Orofacial injury by human bite: experience at a rural health centre - Jajoo, S. N.; Pal, Gaurav (International Surgery Journal, 2017)
Human bite injuries are rare and are usually the result of fight and an inevitable helpless state of opponent who commit such crime. The aim of this article is to present two such cases which were managed at a rural health centre. The first patient is a young 22-year male who was bitten by same age group person over the tip of nose resulting in an avulsion injury. The second case is 29-year male patient was bitten at right upper lip. Both patients were managed at a rural health centre and both had satisfactory results.